2015
DOI: 10.1186/s13000-015-0386-x
|View full text |Cite
|
Sign up to set email alerts
|

A GRIA2 and PAX8-positive renal solitary fibrous tumor with NAB2-STAT6 gene fusion

Abstract: Solitary fibrous tumor (SFT) is a rare neoplasm composed of mesenchymal-derived spindle cells. Although SFT occurs anywhere in the body, they most frequently affects the thoracic region. Here, we reported an extremely rare case of an extrathoracic SFT occurring primarily in the kidney. To our knowledge, little information has been described on the immunohistochemistry (IHC) and genetics of renal SFT.A 41-year old Japanese female came to our hospital for further examination of a left kidney mass detected incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…8,15 Ranking the second, NAB2ex4-STAT6ex2 still occurred in one third of our cases. Intriguingly, the detection rate of other miscellaneous fusion variants appeared dependent on different sub-sites of extrathoracic SFTs, which, in our series and when combined with previously documented cases (Table 3), 4,8,[16][17][18][19][20][21] was both significantly rare for body cavity-based tumors. This finding was in sharp contrast with SFTs occurring in the head and neck, where various miscellaneous variants were In the presence of amplifiable housekeeping PGK mRNA, cases 11-15 showed no detectable fusion transcript by RT-PCR (right gel).…”
Section: Discussionsupporting
confidence: 71%
“…8,15 Ranking the second, NAB2ex4-STAT6ex2 still occurred in one third of our cases. Intriguingly, the detection rate of other miscellaneous fusion variants appeared dependent on different sub-sites of extrathoracic SFTs, which, in our series and when combined with previously documented cases (Table 3), 4,8,[16][17][18][19][20][21] was both significantly rare for body cavity-based tumors. This finding was in sharp contrast with SFTs occurring in the head and neck, where various miscellaneous variants were In the presence of amplifiable housekeeping PGK mRNA, cases 11-15 showed no detectable fusion transcript by RT-PCR (right gel).…”
Section: Discussionsupporting
confidence: 71%
“…A standard previously reported staining procedure was used. 16 In brief, tissue sections (3 mm) obtained from the FFPE specimens were deparaffinized in xylene and rehydrated. Endogenous peroxidase was blocked with 3% hydrogen peroxide in methanol for 15 minutes.…”
Section: Pathologic Immunohistochemistry and Semiquantitative Evalumentioning
confidence: 99%
“…These findings suggest that the tumor behavior and prognosis of composite PCs are greatly influenced by the type of neural components involved. According to Wang et al ( 40 ), copy number gain (1 to 9 copies more than CEP2 gene) and amplification (at least 10 copies greater than those) of the N-myc gene were observed in 78.1% and 3.1% of 32 patients with GNBLs and NBLs, respectively. They also demonstrated that N-myc gain was a favorable prognostic factor in 220 pediatric patients with neuroblastic tumors, compared with a normal and amplified status of the N-myc gene.…”
Section: Discussionmentioning
confidence: 98%
“…The immunohistochemical staining methods ( 38 , 40 ) and fluorescence in-situ hybridization analyses used in the present report are described in detail in the supplementary file ( Supplementary file 2 ).…”
Section: Case Reportmentioning
confidence: 99%